2020
DOI: 10.3390/jcm9020348
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Medication Review Including Deprescribing for Older Patients in an Emergency Department: A Longitudinal Feasibility Study

Abstract: Medication review for older patients with polypharmacy in the emergency department (ED) is crucial to prevent inappropriate prescribing. Our objective was to assess the feasibility of a collaborative medication review in older medical patients (≥65 years) using polypharmacy (≥5 long-term medications). A pharmacist performed the medication review using the tools: Screening Tool of Older Persons’ potentially inappropriate Prescriptions (STOPP) criteria, a drug–drug interaction database (SFINX), and Renbase® (ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 57 publications
4
44
0
Order By: Relevance
“…The physician implemented 69% of the recommended deprescribed medications by the clinical pharmacist. This is within the implementation range of 61–90% reported by other studies with collaboration between pharmacists and physicians [ 16 , 24 , 25 ]. Considering the subacute setup for patients with symptoms requiring treatment, our reported implementation rate of 69% indicates that collaboration between pharmacists and physicians is feasible.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The physician implemented 69% of the recommended deprescribed medications by the clinical pharmacist. This is within the implementation range of 61–90% reported by other studies with collaboration between pharmacists and physicians [ 16 , 24 , 25 ]. Considering the subacute setup for patients with symptoms requiring treatment, our reported implementation rate of 69% indicates that collaboration between pharmacists and physicians is feasible.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, in a Danish longitudinal feasibility study by Houlind et al, 1.6 medications were on average deprescribed based on a pharmacist–geriatric medication review intervention in the emergency department. The most frequently deprescribed medications observed by Houlind et al were proton pump inhibitors, analgesics, antihypertensives, and statins [ 16 ]. In contrast to our study, Marvin et al and Houlind et al found no difference in the total number of medications prior to intervention and during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that discontinuing sleep and depressive drugs can improve cognitive function in this population [ 53 ]. As polypharmacy can be easily missed during acute treatment, healthcare professionals should carefully assess the number of medications taken by the patient and implement active measures to lower polypharmacy after shared decision-making with the patients and their families [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study uses data collected as part of FAM-CPH , an observational cohort study aiming to investigate mechanisms of biological aging and chronic inflammation, as well as malnutrition, and medication in acutely ill and healthy older adults as well as healthy young adults. Previous results from FAM-CPH regarding drug prescription have been published elsewhere [ 27 ]. FAM-CPH was approved by the Health Research Ethics Committee for the Capital Region of Denmark (H-16038786), the Danish Data Protection Agency (AHH-2016-067) and was registered at Clinicaltrials.gov (NCT03052192).…”
Section: Methodsmentioning
confidence: 99%